2021
DOI: 10.3390/ijms22042065
|View full text |Cite
|
Sign up to set email alerts
|

Computational Selectivity Assessment of Protease Inhibitors against SARS-CoV-2

Abstract: The pandemic of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a serious global health threat. Since no specific therapeutics are available, researchers around the world screened compounds to inhibit various molecular targets of SARS-CoV-2 including its main protease (Mpro) essential for viral replication. Due to the high urgency of these discovery efforts, off-target binding, which is one of the major reasons for drug-induced toxicity and safety-related drug attrition, was neglected. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…The FXa and thrombin show considerable similarity to M pro binding site, as judged by the 3D superimposition of their structures with a good correlation (Fig. 1A) and in line with previous literature 22,23 . Thus, we interrogated if the M pro (and as a control papain-like protease, PL pro ) was susceptible to direct inhibitors of FXa (apixaban and rivaroxaban) and thrombin (dabigatran).…”
Section: Apixaban Non-competitively Inhibits Sars-cov-2 M Prosupporting
confidence: 89%
See 3 more Smart Citations
“…The FXa and thrombin show considerable similarity to M pro binding site, as judged by the 3D superimposition of their structures with a good correlation (Fig. 1A) and in line with previous literature 22,23 . Thus, we interrogated if the M pro (and as a control papain-like protease, PL pro ) was susceptible to direct inhibitors of FXa (apixaban and rivaroxaban) and thrombin (dabigatran).…”
Section: Apixaban Non-competitively Inhibits Sars-cov-2 M Prosupporting
confidence: 89%
“…The main protease (M pro ) of SARS-CoV-2 is considered as one of the main targets for drug repurposing, due to its cleavage activity at eleven sites at the viral polyprotein 22 . Curiously, FXa and thrombin share a considerable similarity to SARS-CoV-2 M pro binding site (according to the respective dimensionless scores of 0.71 and 0.74, in a maximum of 1.00).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that elevated levels of FXa are related not only to hypercoagulability in patients with severe COVID-19, but also to inflammatory exacerbation and viral infection mechanisms, what positions FXa inhibitors as a potential prophylactic and therapeutic treatment for high-risk patients with COVID-19 45 . Furthermore, considerable active site similarity based on 3D fingerprints and the positioning of catalytic residues was observed between the FXa protease and the 3CL protease 46 , and three FXa inhibitors were screened as potential inhibitors of 3CL pro in an in silico molecular docking of ligand selection 47 .…”
Section: Discussionmentioning
confidence: 99%